Informed consent in dental care and research for the older adult population: A systematic review - Mukherjee, Amrita (J Am Dent Assoc, 2017)
BACKGROUND: Ethics in health care and research is based on the fundamental principle of informed consent. However, informed consent in geriatric dentistry is not well documented. Poor health, cognitive decline, and the passive nature of many geriatric patients complicate this issue. METHODS: The authors completed this systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The authors searched the MEDLINE PubMed, Web of Science, PsycINFO, and Cochrane Library databases. The authors included studies if they involved participants 65 years or older and discussed topics related to informed consent beyond obtaining consent for health care. The authors explored informed consent issues in dentistry and other biomedical care and research. RESULTS: The authors included 80 full-text articles on the basis of the inclusion criteria. Of these studies, 33 were conducted in the United States, 30 addressed consent issues in patients with cognitive impairment, 29 were conducted in patients with medical issues, and only 3 involved consent related to dental care or research. CONCLUSIONS: Informed consent is a neglected topic in geriatric dental care and research. Substantial knowledge gaps exist between the understanding and implementation of consent procedures. Additional research in this area could help address contemporary consent issues typically encountered by dental practitioners and to increase active participation from the geriatric population in dental care and research. PRACTICAL IMPLICATIONS: This review is the first attempt, to the authors’ knowledge, to identify informed consent issues comprehensively in geriatric dentistry. There is limited information in the informed consent literature covering key concepts applicable to geriatric dentistry. Addressing these gaps could assist dental health care professionals in managing complex ethical issues associated with geriatric dental patients.